2015
DOI: 10.1038/gim.2014.178
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution copy-number variation resource for clinical and population genetics

Abstract: Purpose Chromosomal microarray analysis to assess copy number variation (CNV) has become a first tier genetic diagnostic test for individuals with unexplained neurodevelopmental disorders (NDD) or multiple congenital anomalies (MCA). Over 100 cytogenetic labs worldwide use the new ultra-high resolution Affymetrix CytoScan-HD array to genotype hundreds of thousands of samples per year. Our aim was to develop a CNV resource from a new population sample, which would enable more accurate interpretation of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
65
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 19 publications
(22 reference statements)
1
65
3
Order By: Relevance
“…Of note, there is no frequency information available for the 13q12 deletion in 1000 Genomes, which suggests that the precise population frequency of this CNV is not well known. However, we found three studies in DGV, which reported CNVs in controls with > 50% reciprocal overlap with the CNV in our study (Cooper et al , 2011, Uddin et al , 2015, Pinto et al , 2007). While we cannot rule out a possible AN diagnosis in these individuals, 13q12 deletion does not appear to be AN specific, and its presence in one AN case should be interpreted with caution as larger case-control samples are required to rigorously evaluate the validity of this deletion in AN.…”
Section: Discussioncontrasting
confidence: 59%
“…Of note, there is no frequency information available for the 13q12 deletion in 1000 Genomes, which suggests that the precise population frequency of this CNV is not well known. However, we found three studies in DGV, which reported CNVs in controls with > 50% reciprocal overlap with the CNV in our study (Cooper et al , 2011, Uddin et al , 2015, Pinto et al , 2007). While we cannot rule out a possible AN diagnosis in these individuals, 13q12 deletion does not appear to be AN specific, and its presence in one AN case should be interpreted with caution as larger case-control samples are required to rigorously evaluate the validity of this deletion in AN.…”
Section: Discussioncontrasting
confidence: 59%
“…The deletion of 22q13.3 is a definitive cause for ASD and deletion of the SHANK3 gene specifically is a major cause of the Phelan-McDermid syndrome. The de novo duplication of 16p13.2 has been associated with ASD in a recent report [36] and also found rarely in a control population[37]. The patient's overall clinical presentation is consistent with PMS.…”
Section: Discussionmentioning
confidence: 67%
“…These duplications spanned the genes MCHR2 and MCHR2‐AS1 . In the Database of Genomic Variants (DGV; http://dgv.tcag.ca/dgv/app/home), five studies report at least one duplication affecting MCHR2 (http://www.1000genomes.org/home). In total, 12 duplications were observed in 57 328 individuals (0.02%).…”
Section: Discussionmentioning
confidence: 99%
“…This strategy reduces type I errors, whereas type II errors are expected to increase. http://dgv.tcag.ca/dgv/app/home), 26 five studies report at least one duplication affecting MCHR2 [27][28][29][30] (http://www.1000genomes.org/ home). In total, 12 duplications were observed in 57 328 individuals (0.02%).…”
Section: Discussionmentioning
confidence: 99%